EFEKTIVITAS MODEL PEMBELAJARAN PROJECT BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN DESAIN GRAFIS - Harahap, Ahmad Indra; Andrean, Andrean; Figna, Harry Pratama (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2024)
This research aims to determine the effectiveness of the Project Based Learning learning model in improving student learning outcomes, especially in graphic design learning with a step-by-step approach to the Project Based Learning model. This research uses a quantitative approach with a whole group comparison design experimental method. This research uses an instrument in this research in the form of a questionnaire. Then the data was analyzed using the Independent Sample t-test.